The Role of The State in Improving Welfare with Giving Salary of Lecturers At Private Universities - Ahmadin Ahmadin (STKIP Taman Siswa Bima, 2024)
Swata Higher Education in providing higher education and research as well as community service are activities in an effort to produce educated people. Research, which is also a research activity that adheres to the rules in an effort to find the truth and solve problems in science, technology or the arts, as well as its service to society, certainly encourages people to live a cultural life. Apart from that, it can also provide reasoning and scientific principles in personal development in the midst of national society. The aim of this research is to explore in depth and encourage a better understanding of the important role that the State can take in ensuring welfare and providing fair salaries for lecturers who teach at private universities. The type of legal research used in this research is normative research. This means that the starting point of the research is an analytical study of statutory regulations related to the issues raised. The approach methods used in this research are the statutory approach, the conceptual approach and the sociological approach (Sociological Jurisprudence). Then the results of this research are that there is a gap between the policies implemented by the government regarding the wages of lecturers at state universities and private universities by looking at the binding regulations in managing universities. One of them is by providing wages to lecturers at State Universities, where the government provides basic wages (salaries), allowances, certification and sufficient remuneration. Meanwhile, the government only charges private universities with certification allowances. Then wages are given by the higher education institution where the lecturers serve according to their abilities at the higher education institution.